O “FANTASMA” da transparência: comunicação pública no Portal da Transparência da Assembleia Legislativa do Maranhão – ALEMA - SANTOS, Asmynne Bárbara Barbosa dos (2017)
With the approval of the Acess To Information Law (AIL), the theoretical reflection about the right to information has intensified, since the law has impacted not only the citizen, who had access to the data and documents produced by and under custody of the State - with the exception of those that have a personal nature or classified - but also the public management, which had to adopt measures and tools to achieve public transparency. Access to information is an essential right and is linked to the notion of democracy, anchored in the constitutional principle of publicity of the public acts. This dissertation analyzes the Public Communication in the effectiveness of the right to information, through the use of a digital tool called Portal da Transparência (Transparency Portal). The theoretical approach finds support on the following researchers, among others: Zémor (1995), Matos (2011), Bresser Pereira (2004). The methodology used is qualitative case stu dy about the reaction of the Legislative Council of Maranhão (ALEMA) on “ghost employees” case. It is understood that there is a formal fulfillment of the FOI; however, it is still timid the effective work of Public Communication on the ALEMA portal with the intention to encourage social participation.